IMMUNONOLOGICAL EVALUATION AND ACUTETOXICITY STUDY WITH FERTILITY EXAMINATION FORTHE EFFECT OF AQUEOUS EXTRACT FROM DRIEDFRUITS OF Piper nigrum L. IN MICE - Al Tae’e, Maha; K., Zaid; W., Hadeel (Iraqi Journal of Science, 2024)
The research work was conducted to investigate the effect of oral administrationof water extract of black pepper at doses of (1, 5) mg/kg body weight for two weeksdaily by determining the genotoxic effect (mitotic index), evaluation ofimmunological effect (IgG, IgM, IgA, C3, C4) and measuring fertility hormones(follicles stimulation hormone/FSH, lutenising hormone/LH) levels withhistopathological examinations of female albino swiss mice ovaries in comparisonwith control (normal saline). A clear effect in increasing mitotic activity was reveledfor both doses in comparison with control. Results also showed a significantincrease in the value of the all immunological parameters at both doses incomparison with control. Also obvious raise was seen in the level of FSH and LHfor both doses when compared with normal saline treated mice with no significantdamage seen in female ovaries tissue, in fact there were certain clinicopathologicalchanges in mice ovaries tissue which were represented by increasing in the numbersof primary and secondary follicles and in the numbers of corpus luteum at bothdoses.